2001
DOI: 10.1109/81.904882
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of waveform fractal dimension algorithms

Abstract: The fractal dimension of a waveform represents a powerful tool for transient detection. In particular, in analysis of electroencephalograms and electrocardiograms, this feature has been used to identify and distinguish specific states of physiologic function. A variety of algorithms are available for the computation of fractal dimension. In this study, the most common methods of estimating the fractal dimension of biomedical signals directly in the time domain (considering the time series as a geometric object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
248
0
22

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(275 citation statements)
references
References 13 publications
(20 reference statements)
5
248
0
22
Order By: Relevance
“…For ZC and SSC, the thresholds values used were 0.0005 and 0.001, respectively. Other parameters were chosen according to the literature, such as: for AR (order = 4), DFA (L = 10), PSR (N = 20) (Phinyomark et al, 2013); and HFD (Kmax = 10) (Esteller et al, 2001). Additionally, the classifier's parameters were optimized as: for KNN (K = 9) and for SVM (C = 0.01 and polynomial kernel with order 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For ZC and SSC, the thresholds values used were 0.0005 and 0.001, respectively. Other parameters were chosen according to the literature, such as: for AR (order = 4), DFA (L = 10), PSR (N = 20) (Phinyomark et al, 2013); and HFD (Kmax = 10) (Esteller et al, 2001). Additionally, the classifier's parameters were optimized as: for KNN (K = 9) and for SVM (C = 0.01 and polynomial kernel with order 3).…”
Section: Resultsmentioning
confidence: 99%
“…DFA offers advantage over methods based on wavelet transformations in the time-scale domain (Phinyomark et al, 2012b). On the other hand, HFD (Esteller et al, 2001) is one of the most used fractal dimension feature, as it has shown better performance than other fractal methods (Esteller et al, 2001), and has also shown good performance in the classification of EMG signals.…”
Section: Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fractal dimension was calculated using the procedure reported by Higuchi [8] for irregular time series. This procedure yields a more accurate estimation of fractal dimension [12].…”
Section: Methods Two: Identification Of Hand Gestures Using Semg Recormentioning
confidence: 99%